Identifikasi Corporate Social Responsibility Dan Green Human Resource Management PT Telkom Indonesia - Antony Sentoso; Jhohari Jhohari; Lara Meilani; Melissa Melissa; Nasyah Amanda; Winna Angelina (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The rapid development of the world and industry has made companies face challenging conditions where they must carry out socially responsible business practices. This form of social responsibility can be realized through the implementation of Corporate Social Responsibility (CSR) and Green Human Resource Management (GHRM). PT Telkom Indonesia as the largest telecommunications company in Indonesia has consistently implemented these two things which are in line with its obligations as a BUMN to support efforts to improve government performance. The research method used is literature review using information obtained from previous research and official websites. The results obtained from this analysis are that PT Telkom Indonesia has a series of CSR programs that are dominantly oriented towards community welfare and the implementation of GHRM practices within the company to support the achievement of sustainable development goals.